Caracterización físico química de las borras de hidrocarburos generadas en la actividad petrolera locación 2A Lote 95 - Ruiz Laulate, Zila Zelenita (2024)
This research addresses the physicochemical characterization of hydrocarbon sludge generated in Location 2A - Lot 95 of PETROTAL PERÚ S.R.L., with the aim of determining the contaminant potential of these residues in the environment. The main objective of the study is to evaluate the chemical characteristics of the petroleum sludge produced at this location and to compare the results with the Soil Environmental Quality Standards of MINAM. A methodology was applied that included an exhaustive review of the existing literature on the characterization and treatment of hydrocarbon sludge. Additionally, the information provided by the company was analyzed, and an on-situ visit was made to the Bretaña oilfield - Lot 95, where nine sampling points were selected for sample collection, which were then sent to a laboratory for analysis, then analyzed using tables and graphs generated in Microsoft Excel. The results revealed high concentrations of organic matter in the sales tanks and sumps. Heavy metals such as Barium and Chromium, as well as total petroleum hydrocarbons (TPH) and BETX compounds, exceeded the standards in all analyzed tanks. It is concluded that the hydrocarbon sludge in Location 2A represents a significant environmental risk, emphasizing the need to implement appropriate management strategies.